Analisis Tingkat Kepuasan Penumpang terhadap Kualitas Layanan di Pelabuhan Feri Kendari- Wawonii - Satyadharma, Maudhy (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2024)
Indonesia as an archipelagic country requires reliable sea transportation. One of the means of sea transportation is the port. One of the roles of the port is the main gateway for the flow of goods, both exports and imports, and the transfer of cargo between modes of transportation and plays an important role in the country's economy to create economic growth. This research aims to analyze passenger satisfaction with the quality of services provided at the Kendari-Wawonii Ferry Port. The implementation method is quantitative descriptive. The research sample was 384 passengers who referred to Permenpan RB Number 14 of 2017 concerning Guidelines for Preparing Community Surveys for Public Service Organizing Units. The research results found that public satisfaction at the Kendari-Wawonii Ferry Port in 2023, which is mandated by Law Number 25 of 2008 concerning Public Services, by assessing 9 elements resulted in a figure of 76,824 (not good). The elements that received the highest scores were the system elements, mechanisms and procedures, while the elements that received the lowest scores by the research respondents were the complaint handling elements and the facilities and infrastructure elements.